AS INSTITUIÇÕES DE ENSINO SUPERIOR DA CIDADE DE GUARUJÁ (SP) E A INSTITUCIONALIZAÇÃO DAS ATIVIDADES DE EXTENSÃO - Santos, Glauber de Almeida Freitas (2014)
This work aims to analyze the overall institutionalization of university extension, with a focus on private higher education institutions in the city of Guarujá (SP). The research is justified by the importance that the extension made in the context of education in Brazil, considering that the tripod of teaching consists of Research, Education and Extension. The guiding question is: How does the institutionalization of university extension projects has been given in the IES Guarujá SP. Specific objectives were defined: a) Identify political ideas as well as the practical extension declared by IES b) Analyse the vision of the manager in the administration of extension with respect to its institutionalization. The methodological approach to be developed will be the qualitative research, exploratory, using the methodology of multiple case studies. The documentary research and semi-structured interviews are part of the data collection that will subsidize the final analysis. Assumptions as field research that will have a cross-analysis of data: 1) The implementation of extension projects is carried out only for bureaucratic and political comply with legal requirements and 2) the institutionalization of extension projects is done only with slow lawful purposes and / or politicians to meet a portion of the population in the vicinity of the institution, but without legitimate social purposes regarding the essence of the values of university extension. The results of the field research, the assumptions have been confirmed in the IES study as well as the absence of the inseparability.